Increased messenger Rna levels for low-density lipoprotein receptor and 3-hydroxy-3-methylglutaryl coenzyme A reductase in rat liver after long-term ethanol ingestion - Seitz, Helmut K.; Kuhn, Bernhard; Hodenberg, Eberhard von; Fiehn, Walter; Conradt, Christian; Simanowski, Ulrich (Hepatology, 1994)
Because long-term alcohol intake leads to severe alterations of cholesterol metabolism resulting in both elevated serum cholesterol levels and increased hepatic concentrations of cholesterol esters, we investigated the effect of long-term ethanol consumption on the hepatic messenger RNA (mRNA) content of 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase and low-density lipoprotein receptor, two major regulatory factors in cholesterol metabolism, and of apoprotein E. Twenty-four male Sprague-Dawley rats were pair-fed nutritionally adequate liquid diets containing 36% of total calories as either ethanol or isocaloric carbohydrates for 3 wk. In addition, the lipid content of the diets was varied, resulting in 35%, 17.5%, and 8.8% of total calories corresponding to a daily intake of cholesterol of between 1.2 and 6.3 mg/kg body wt. Although increasing dietary cholesterol intake resulted in a significant decrease of hepatic mRNA for low-density lipoprotein receptor and HMG-CoA reductase (p<0.05), long-term ethanol consumption led to a significant increase of the mRNAfor both proteins(p<0.01), and this increase was predominantly obvious in animals fed a low-cholesterol diet. In contrast, mRNA content of apoprotein E was found to be significantly lower in livers from rats fed ethanol for a prolonged period of time as compared with controls (p<0.01), and this effect was found to be still present, although less pronounced, after low cholesterol intake. These findings were paralleled by a significant increase in hepatic cholesterol esters (161 ± 30 vs. 70 ± 25 mg/100 gm; p<0.01) but not free cholesterol and by elevated serum cholesterol levels (129 ± 8 vs. 85 ± 10 mg/100 ml; p<0.01). The data show that long-term ethanol consumption results in enhanced hepatic mRNA levels of low-density lipoprotein receptor and HMG-CoA reductase, two determinants of cholesterol metabolism, which may contribute to hepatic cholesterol accumulation and hypercholesterolemia frequently seen in the alcoholic. (Hepatology 1994;20:487-493.)